The application of the tribal law tada hera by the village government in the village of Habi district Kangae - Avia, Aurelia; Natsir Rodja, Abdul; Aswin, Danar (Lembaga Riset Mutiara Akbar, 2022)
The purpose of this study was to find out how the implementation of tada hera customary law by the village government and to find out how the effectiveness of the implementation of tada hera customary law by the village government. The type of research used is descriptive qualitative research using primary data sources. Primary data sources obtained from interviews are village heads, BPD, traditional institutions, community leaders. and secondary is data that does not directly provide data for data collection, in the form of documentation and photographs and then presented in the form of descriptive analysis where the data generated from primary and secondary data sources are described and provide an appropriate picture of the reality in the field to then produce conclusions. The results of the study prove that first, the role of the village government in the process of implementing the settlement of violations of customary law in the village of Habi related to tada hera, namely bridges and peace judges between the two parties who are having problems. In solving the problem, the village government must be neutral and not take sides with any party. Second, the implementation of customary law by the village government is always guided by the Village Regulation No. 02 of 2005, it is actually implemented and obeyed by the community